Phenolic compounds of Eugenia involucrata (Myrtaceae) extracts and associated antioxidant and inhibitory effects on acetylcholinesterase and α-glucosidase. Issue 4 (24th November 2020) - Cipriani, Andreza; Sousa, Adrieli Luz de; Tenfen, Adrielli; Siebert, Diogo Alexandre; Gasper, Andre Luis de; Vitali, Luciano; Micke, Gustavo Amadeu; Alberton, Michele Debiasi
Abstract: Eugenia involucrata DC. (Myrtaceae), popularly known as "cereja-do-Rio-Grande", is a native tree from Brazil, popularly used as a hypoglycemiant. Crude hydroalcoholic extract (CHE) and fractions (insoluble (FI), dichloromethane (FDM), ethyl acetate (FEA) and butanol (FBu)) of leaves were assessed to determine the phenolic chemical composition by HPLC-ESI-MS/MS. 10 compounds were identified, being 7 new for this species: rutin, isoquercitrin, luteolin-7- O -rutinoside, mandelic acid, naringenin, luteolin-7- O -glucoside and salicylic acid. Extract and fractions showed inhibitory activity on acetylcholinesterase (AchE) enzyme (best result: IC50 = 44.19 µg mL −1, for FEA) and α-glucosidase (α-Glu) (best result: IC50 = 31.25 ± 0.15 µg mL −1, for CHE). The observed antioxidant and inhibitory activity on the AchE and α-Glu is due to, at least in part, the presence of phenolic compounds in the samples. Graphical Abstract: